Percepção de cirurgiões-dentistas em serviços de emergência odontológica: o atendimento a mulheres vítimas de violência interpessoal - Silvilene Giovane Martins Pereira (2022)
INTRODUCTION: Violence is a phenomenon that has been taking alarming proportions in the world, being internationally considered a public health problem and a violation of women's human rights. The literature shows that among health professionals, the dental surgeon (DC) has a good chance of identifying cases of women in situations of violence, since the dental examination involves the evaluation of the oral cavity and adjacent structures, and trauma maxillofacial is one of the main injuries observed in these cases. Considering the role of health care, in the recognition and care in these cases, it is of fundamental importance to carry out research that allows the expansion of knowledge about this phenomenon, especially in relation to the performance of the CD. OBJECTIVE: To evaluate the dentist's perception and attitude towards the care of women in situations of interpersonal violence, who presented maxillofacial trauma. METHODS: Qualitative study, carried out through a scope review in order to map what has been produced in the literature on the care provided by the CD, in emergency health services, when caring for women in situations of violence. RESULTS: Of the 48 studies retained, thirteen were included, published between 2001 and 2018. Of the 13 articles included, seven were cross-sectional studies, two were qualitative studies, three were literature reviews and a theoretical discussion. Six articles have CDs as their population exclusively. The others evaluate health professionals, including the DCs. The results revealed that the CD is essential in the fight against violence against women, as it is the health professional who is most able to identify these cases, since their area of activity, head and neck, are those in which the signs of violence are more present. However, the perception and attitude of the CD regarding the care of women in situations of interpersonal violence are flaws and these professionals are still not prepared and qualified to deal with the problem. As a final part of the study, a Professional Guiding Guide was created to assist women in situations of interpersonal violence. The guide was theoretically based on the scope review. CONCLUSIONS: The recognition of cases of women in situations of violence by the CD requires the incorporation of educational measures that provoke cultural changes that involve the development of actions aimed at the deconstruction of stereotypes, the transformation of gender norms and the denaturalization of this social phenomenon by the professional CD.